F. Gregory Gause III, The International Relations of the Persian Gulf, Nueva York, Cambridge University Press, 2010, 258 pp. - Viramontes Viramontes, Erick (El Colegio de México, 2012)
F. Gregory Gause III, The International Relations of the Persian Gulf, New York, Cambridge University Press, 2010, 258 pp.